Magnetic topologies of an in vivo FTE observed by Double Star/TC‐1 at Earth's magnetopause. Issue 14 (26th July 2013) - Pu, Z. Y.; Raeder, J.; Zhong, J.; Bogdanova, Y. V.; Dunlop, M.; Xiao, C. J.; Wang, X. G.; Fazakerley, A.
Abstract [1] Flux transfer events (FTEs) are magnetic flux ropes formed at planetary magnetopauses (MPs). Although evidence suggests that FTEs form through time‐dependent magnetic reconnection, details of that process and 3D structure of the flux ropes remain largely unclear. This letter presents Double Star/TC‐1 data of an FTE occurred on 7 April 2004 which show that the FTE was separated by two X‐lines moving south‐dawnward. In particular, the electron energy‐pitch angle distribution implies that the FTE was composed of flux ropes of all four possible magnetic topologies, indicating that the field lines must have reconnected multiple times. This is an intrinsic property of FTEs formed by 3D multiple X‐line reconnection distinguished from quasi 2D FTE models. This knowledge of FTE magnetic topologies helps to improve our understanding of solar wind‐ magnetosphere coupling at the MP.